2010
DOI: 10.1111/j.1469-8137.2009.03139.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in resynthesized Brassica napus allotetraploids: transcriptional changes do not explain differential protein regulation

Abstract: Summary• Polyploidy, or whole genome duplication, is a major evolutionary process that has shaped eukaryotic genomes, notably those of flowering plants. The mechanisms underlying the regulation of, and sharing of functions between, the duplicated genes originating from polyploidy events, which lead to novel phenotypes, remain to be elucidated.• A previous comparative proteomic study identified 360 proteins that were differentially regulated between the diploid Brassica progenitors and their synthetic allotetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 52 publications
7
60
1
Order By: Relevance
“…In the proteomic analysis, a major latex protein-like protein, major latex protein-like 423 (At1g24020), was highly expressed in A. arenosa (Aa/At4¼4.322 ± 0.318) but downregulated in the allotetraploids (F 1 /MPV¼0.437 ± 0.074; F 8 / MPV¼0.306±0.066), which was consistent with the microarray data of upregulation or downregulation at the transcript levels (Supplementary Tables S3 and S5). Interestingly, similar findings were found in resynthesized B. napus allotetraploids (stem tissues) using protein two-dimensional analysis (Albertin et al, 2006) and semi-quantitative reverse transcriptase-PCR assays (Marmagne et al, 2010). Finally, expression of 3 (B37.5%), 59 (B47.2%) and 18 Proteins identified in both runs (overlap) were used for expression divergence analysis.…”
Section: Comparison Of Proteomic With Transcriptomic Datamentioning
confidence: 52%
See 2 more Smart Citations
“…In the proteomic analysis, a major latex protein-like protein, major latex protein-like 423 (At1g24020), was highly expressed in A. arenosa (Aa/At4¼4.322 ± 0.318) but downregulated in the allotetraploids (F 1 /MPV¼0.437 ± 0.074; F 8 / MPV¼0.306±0.066), which was consistent with the microarray data of upregulation or downregulation at the transcript levels (Supplementary Tables S3 and S5). Interestingly, similar findings were found in resynthesized B. napus allotetraploids (stem tissues) using protein two-dimensional analysis (Albertin et al, 2006) and semi-quantitative reverse transcriptase-PCR assays (Marmagne et al, 2010). Finally, expression of 3 (B37.5%), 59 (B47.2%) and 18 Proteins identified in both runs (overlap) were used for expression divergence analysis.…”
Section: Comparison Of Proteomic With Transcriptomic Datamentioning
confidence: 52%
“…A recent study using proteome and transcriptome analysis in single Escherichia coli cells suggested that protein and mRNA copy numbers in single cells for any given gene are uncorrelated, displaying a substantial amount of intrinsic and extrinsic noises (Taniguchi et al, 2010). Comparison of transcriptomes using semiquantitative and quantitative PCR assays and two-dimensional protein gel electrophoresis in B. napus also revealed that the majority of transcript changes (B62%) did not reflect the differential protein accumulation in the resynthesized allotetraploids compared with the diploid progenitors, B. oleracea and B. rapa (Marmagne et al, 2010). Changes in genome structure, gene expression and interphase organization have also been documented in A. thaliana trisomics (Huettel et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we propose that higher transcript levels of AOX1b protein could reflect earlier programmed flowering. Transcriptomic analysis in response to S restriction should be integrated with a metabolomic approach because, as in the oilseed rape, most genes are not expressed additively at the protein level (Marmagne et al 2010). Such differences between the transcription and expression of bypass proteins (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression was found to vary greatly from parent levels in a non-additive fashion in the early stages of synthetic B. napus formation (Albertin et al 2006), but with overall conservation of gene networks and pathways and protein functionality (Albertin et al 2007). The differential regulation of protein expression in synthetic allopolyploids has been attributed to post-transcriptional modification rather than transcriptional changes, perhaps through the small RNA pathway (Marmagne et al 2010). In addition, de novo variation in phenotypic traits in response to different growth conditions has been found in B.…”
Section: Introductionmentioning
confidence: 99%